Análise Trifásica de Sistemas de Distribuição com Modelos de Turbinas Eólicas Tipo IV - Rocha, Ednardo Pereira da (2015)
The connection of wind generators might cause significant influences in the profile voltages, voltage unbalance, loading and the electrical losses in radial power distribution systems. This fact requires a specific study, called Hosting Capacity, which aims to analyze the maximum limit of the power increase on the network that makes the performance of the system acceptable to the established quality limits. This work shows an IEEE radial distribution system behavior, composed of 13 bus, in steady state, when a synchronous wind machine is engaged on the bus 680 in two ways: directly connected to the network and connected through the frequency converter. For each type of connection the power factor was varied from 0.9 capacitive to inductive 0.9. The parameters analyzed in connection bar were the degree of voltage unbalance, the losses in the system and the profile of voltages on the bus 680 for each case . The simulations were performed using the program Distribution Network Analysis with Generation Aeolian-Electric - ANAREDGEE, which was developed and validated with own results of the IEEE. It was found that there was a reduction in the degree of unbalance for all simulated situations, when compared to the original value of the system status, not exceeded the limits determined by imbalances entities NEMA, ANSI, IEEE and ANEEL. Regarding the profile of voltages in the various system buses, there was a slight decrease in some situations. In the original system, the voltage level of the phase B in the bus 680 exceeded the 5% voltage given by ANEEL, with a value of 1.0529 p.u. With the machine connected directly, there was an increase of this value in all simulations with different power factor, while the connection through frequency converter might causa a reduction of the phase B voltage levels to below 1.05 pu in situations where the power factors were equal to 0.9 capacitive and unitary. The system losses were reduced in all cases, but showed lower values when the synchronous machine was integrated into the system by frequency convertor. It was also observed a significant reduction in the degree of system imbalance after connecting the synchronous machine, this reduction, in most cases, occurred in proportion to the increase in power injected into the connection bar